2(x + 4)(x - 10)
A quadratic polynomial.
yes
2x2+6x-8 = 72 2x2+6x-8-72 = 0 2x2+6x-80 = 0 (2x-10)(x+8) = 0
-70
2x2-3x-5 = (2x-5)(x+1) when factored
72 ^ 9x8 ^ ^ 3x3 4x2 ^ 2x2
2(x + 4)(x - 10)
x3 - 2x2 + x - 2 =(x - 2)(x2 + 1)
If you mean: 2x2+7x+5 then it is (2x+5)(x+1) when factored
2(x - 6)(x + 6)
2x2 - 72 would be factored into (2x - 12)(x + 6) or (2x + 12)(x - 6) To double check, multiply each pair: (2x - 12)(x + 6) = 2x2 + 12x - 12x - 72 = 2x2 - 72 (2x + 12)(x - 6) = 2x2 - 12x + 12 x - 72 = 2x2 - 72
A quadratic polynomial.
(x - 2)(2x + 9)
yes
A Quadratic statement
2x2+6x-8 = 72 2x2+6x-8-72 = 0 2x2+6x-80 = 0 (2x-10)(x+8) = 0